Pattern of vigorous physical activity among Egyptian freshmen university students - Montasser, Nadia Abd El-Hamed; El- Fattah, Abdel-Hady El-Gilany Abd; Helal, Randah Mohamad (South African Journal of Sports Medicine, 2011)
Objectives. To highlight the pattern of vigorous physical activity among freshmen university students and to evaluate the association between sociodemographic factors, perceived barriers, support factors, sedentary behaviours and body mass index. Methods. A cross-sectional study was conducted on Mansoura University students at the beginning of the academic year 2008 - 2009. A total of 500 freshmen students were selected by systematic random sample. Participants responded to the short form of International Physical Activity Questionnaire and other questions. Results. The study revealed that the prevalence of vigorous activity among the students was 9.8% (N=49) versus 90.2% (N=451) for mild and moderate activity. Body-related barriers were significantly higher among those reporting mild and moderate activities as shyness from others when doing exercise (6.9% versus 0.0%) and shyness from body looks in front of people (14.6% versus 4.1%). Lack of equipment was also perceived to be a barrier (31.0% versus 16.3%), for those doing mild to moderate versus vigorous, respectively. A significantly higher proportion of persons doing vigorous activity reported the influence of support factors such as perceived benefit for health (53.1% versus 33.7%), encouragement from others (53.1% versus 30.4%) and participation from others (51.0% versus 23.9%), compared with the more sedentary students. The majority of both groups spent <4 hours daily in front of a computer, but the overall proportion was significantly higher among those only reporting mild and moderate activity (88.0% versus 63.3%). Conclusion. The prevalence of most of the barriers studied was higher among those reporting mild and moderate activities and support factors were higher among those reporting vigorous activity. These results highlight the importance of environmental factors, social norms and intra-personal factors in determining the pattern of activity among Egyptian freshmen university students. SAJSM, vol 23 No. 4 2011